ACTUALISING VILLAGE POTENTIAL THROUGH UMKM EDUCATION AND PROMOTION - Rita Hayati; Dwi Apriyanti Kumalasari; Zeni Zainal Muis; Al-Amin (Adiba Aisha Amira, 2024)
Actualising village potential through MSME education and promotion is an effort to realise and develop the resources and capabilities of a village, with a focus on empowering Micro, Small and Medium Enterprises (MSMEs). This process involves learning activities (education) to improve the knowledge and skills of MSME actors, as well as marketing strategies (promotion) to introduce and market the products or services of village MSMEs to a wider market. The goal is to increase local economic capacity, encourage product innovation, expand market reach, and ultimately improve the welfare of village communities through sustainable MSME development. The research method in this study is literature. The results show that structured and sustainable education, including training in business management, product innovation, and digital marketing, is crucial in improving the competitiveness of village MSMEs. Meanwhile, an integrated promotion strategy, utilising both online and offline platforms, has proven effective in expanding the market and increasing the visibility of village products. The research conclusions emphasise the importance of synergy between education and promotion in actualising village potential. This integrated approach not only enhances local economic capacity but also promotes sustainable village development. The implications of this research provide a foundation for the development of policies and programmes aimed at empowering rural economies through strengthening MSMEs.